Research on Permeability Coefficient of Heterogeneous Geomaterials Based on Digital Images - Bowen Liu; Junbin Chen; Xinpin Ding (Advances in Civil Engineering)
According to the relationship between permeability and porosity of geotechnical materials, a finite element model representing pore and solid particles is generated randomly according to the porosity of a given finite element calculation model. According to Darcy’s law of flow distribution and steady seepage in the finite element random simulation section, the equivalent permeability coefficients at different porosities are calculated, and the relationship between the equivalent permeability coefficient and the porosity of rock and soil is studied. The results show that the equivalent permeability coefficient is proportional to the porosity with the same pore size. In order to study the seepage characteristics of structural planes of nonmaterial geotechnical materials in different strata contact zones, the formulas for calculating the deformation parameters and permeability coefficients of heterogeneous rock masses with single nonmaterial geotechnical materials are deduced theoretically, and the correctness and applicability of the formulas are verified by experiments. The rock mass sample selected in this paper is granite, which is simulated and analyzed by sandstone in the experiment. The results show that the permeability coefficients of coarse sandstone, fine sandstone, and heterogeneous rock mass are different under the same water pressure and confining pressure. This shows that the lithology on both sides of the nonmaterial geotechnical material surface has a significant influence on the permeability of the nonmaterial geotechnical material rock mass; the permeability coefficient of the nonmaterial geotechnical material rock mass decreases with the increase of confining pressure, the numerical change is limited to a certain confining pressure range, and the permeability coefficient tends to be stable when the confining pressure reaches a certain value. Comparing the theoretical calculation value of permeability coefficient of rock mass with the experimental result, it is found that the two values are in good agreement, which indicates the correctness and applicability of the theoretical calculation formula of permeability coefficient of rock mass of single intangible geotechnical material.